2015
DOI: 10.1007/s10508-015-0677-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior Varies Between Same-Race and Different-Race Partnerships: A Daily Diary Study of Highly Sexually Active Black, Latino, and White Gay and Bisexual Men

Abstract: Racial homophily (partnering with those of the same race) has been suggested as contributing to racial disparities in HIV among gay and bisexual men (GBM). Using a daily diary study, we examined racial homophily and its role in anal sexual behaviors in a sample of highly sexually active Black, White, and Latino GBM (N = 294, n = 3107 sexual events). In general, (1) men tended to partner with others of the same race, (2) HIV was more prevalent among men of color, and (3) race acted independent of whether one wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…The authors pointed to ‘common roots’ for this finding in ‘common experiences such as discrimination, cultural norms valuing masculinity, concerns about confidentiality during HIV testing or treatment, low access to HIV drugs, threats of violence or incarceration, and few targeted HIV prevention interventions’ 14. Sociosexual network effects and associations between partnership race characteristics and sexual behaviours may also be important 15. Our findings here also suggest that multiple non-steady condomless anal sex partners are important in understanding differences in HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The authors pointed to ‘common roots’ for this finding in ‘common experiences such as discrimination, cultural norms valuing masculinity, concerns about confidentiality during HIV testing or treatment, low access to HIV drugs, threats of violence or incarceration, and few targeted HIV prevention interventions’ 14. Sociosexual network effects and associations between partnership race characteristics and sexual behaviours may also be important 15. Our findings here also suggest that multiple non-steady condomless anal sex partners are important in understanding differences in HIV.…”
Section: Discussionmentioning
confidence: 99%
“…While homophily cannot explain the emergence of disparities, higher levels of homophily could help maintain higher rates of infection within high prevalence groups due to the racial segregation in sexual networks. 22 Preliminary studies have identified strong racial homophily in the sexual networks of MSM 2325 and YMSM. 26…”
mentioning
confidence: 99%
“…In another diary study, Grov et al (2016) observed the same unexpected pattern among men in New York City, where White men, followed by Black men and, finally, Latino men, demonstrated successively decreasing rates of racial homophily. An important methodological caveat to this study is that sexual partners were only considered when they were reported as casual, rather than as main partnerships.…”
Section: Sexual Partner Selection and Racial Homophilymentioning
confidence: 63%
“…As shown in Figure 2, racial homophily can relate to how closed a sexual network is and therefore the risk for rapid spread of HIV. Racial homophily occurs across different races and ethnicities of sexual minority men , Grov et al 2016, with some research suggesting that the highest rates of homophily occur among Black men (Newcomb & Mustanski 2013, Raymond & McFarland 2009). Indeed, studies generally show the highest rates of racial homophily among Black/African American sexual minority men, followed by White men, and the lowest rates among Latino men (Sudhinaraset et al 2013).…”
Section: Racial Homophily In Sexual Networkmentioning
confidence: 99%
See 1 more Smart Citation